Unlocking the microbiome communities of Banana (Musa spp.) under disease stressed (Fusarium wilt) and non-stressed conditions - Kaushal, Manoj; Swennen, Rony L.; Mahuku, George S. (MDPI, 2020)
We assessed the diversity, structure, and assemblage of bacterial and fungal communities associated with banana plants with and without Fusarium oxysporum f. sp. cubense (Foc) symptoms. A total of 117,814 bacterial and 17,317 fungal operational taxonomy units (OTUs) were identiﬁed in the rhizosphere, roots, and corm of the host plant. Results revealed that bacterial and fungal microbiota present in roots and corm primarily emanated from the rhizosphere. The composition of bacterial communities in the rhizosphere, roots, and corm were diﬀerent, with more diversity observed in the rhizosphere and less in the corm. However, distinct sample types i.e., without (asymptomatic) and with (symptomatic) Fusarium symptoms were the major drivers of the fungal community composition. Considering the high relative abundance among samples, we identiﬁed core microbiomes with bacterial and fungal OTUs classiﬁed into 20 families and colonizing distinct plant components of banana. Our core microbiome assigned 129 bacterial and 37 fungal genera to known taxa.